POTENSI EKSTRAK ETANOLIK KULIT BUAH JERUK NIPIS (Citrus aurantiifolia (Cristm.) Swingle) SEBAGAI AGEN KHEMOPREVENTIF MELALUI PENEKANAN EKSPRESI c-Myc DAN PENGHAMBATAN PROLIFERASI PADA SEL PAYUDARA TIKUS GALUR SPRAGUE DAWLEY TERINDUKSI 7,12-DIMETILBENZ[a]ANTRASENA - Dewi Pratiwi; Novi Hastuti; Niken Nur W; Inna Armandari; Muthi’ Ikawati; Adam Hermawan; Edy Meiyanto (Majalah Obat Tradisional, 2010)
The using of natural-based medicine is growing rapidly in societies. Besides being cheap and affordable, natural-based medicine is relatively safer than the synthetic drugs. Peel of Citrus aurantifolia (Cristm.) Swingle) is one of the chemopreventive agent which contain flavonoids have potency as anticarcinogenic agent. This study is designed to study the potency of Citrus aurantifolia peel ethanolic extract in proliferation inhibition of Rattus norvegicus mammary cell of Sprague Dawley strain which is induced by 7,12-Dimethylbenz[a]anthracene (DMBA). Rats were divided into five groups consist of DMBA treatment, CMC-Na treatment, extract 1500 mg/kgBW treatment, treatment of DMBA+ extract 750 mg/kgBW and DMBA+ extract 1500 mg/kgBW. At the beginning of the tenth week of the study, breasts was isolated and stored in 10% formalin buffer. Observation of cell proliferation was done by AgNOR method. C-Myc expression observed using immunohistochemistry (IHC). Observation of mammary cell with AgNOR method indicated that the treatment of Citrus aurantifolia peel ethanolic extract can inhibit cell proliferation significantly. Dosage 1500 mg/kgBW gave higher inhibition effect than dosage 750 mg/kgBW. IHC result showed that treatment of Citrus aurantifolia peel ethanolic extract decrease the expression of c-Myc. Dosage 750 mg/kgBW gave lower decreasing effect than dosage 1500 mg/kgBW. Citrus aurantifolia peel ethanolic extract inhibited the proliferation of mammary cell induced DMBA through the inhibition of c-Myc expression in dose dependent phenomena so that it is a potential chemopreventive agent.